Die Beplanningsfunksie van die Bestuurder - G. J. Botha (South African Journal of Business Management, 1970)
Management planning essentially involves a systemisation, or a formalisation, of management processes that are taking place. But the process becomes explicit: management must actually say what its objectives are and how they are to be achieved.